Multiple Baseline Design Across Materials-Behaviors-Examiners: Penerapan untuk Kasus Blood Phobia - Yuwanto, Listyo; Santoso, Christine (ANIMA Indonesian Psychological Journal, 2008)
This research was inspired by a sufferer of blood phobia, who needed a psychological help. The subject was a female sufferer. Method used is a combination of a qualitative approach and mul- tiple baseline design across behaviors-materials-examiners. Data were collected through interview, observation, phobia self-test, and the big five personality inventory. Subject was treated with cogni- tive behavior therapy. Result reveals an alteration between baseline phase and treatment phase, thus it can be concluded that the cognitive behavior therapy is appropriate for this blood phobia disorder pa- tient. Penelitian ini dilatarbelakangi seorang penderita fobia darah yang membutuhkan bantuan penanganan. Metode penelitian merupakan kombinasi antara kualitatif dan multiple baseline design across behaviors-materials-examiners. Subjek penelitian satu orang (perempuan). Data diperoleh melalui wawancara, observasi, phobia self-test, dan the big five personality inventory. Bentuk intervensi adalah terapi kognitif perilaku. Hasil penelitian menunjukkan adanya perbedaan antara baseline phase dengan treatment phase, sehingga dapat disimpulkan bahwa terapi kognitif perilaku cukup efektif dalam membantu mengatasi fobia darah yang dialami subjek.